2017
DOI: 10.1161/circulationaha.116.024926
|View full text |Cite
|
Sign up to set email alerts
|

Should We Perform Catheter Ablation for Asymptomatic Atrial Fibrillation?

Abstract: Since the original description of atrial fibrillation ablation, numerous studies have demonstrated the superiority of catheter ablation over pharmacological therapy for maintenance of sinus rhythm in patients with both paroxysmal and persistent atrial fibrillation. However, to date, no randomized studies have been powered to demonstrate a mortality or stroke reduction benefit of rhythm control with catheter ablation over a rate control strategy. The results of such ongoing studies are not expected until 2018 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 116 publications
0
23
0
2
Order By: Relevance
“…Whether (and how) asymptomatic AF patients could benefit from AF ablation still needs to be established. Incidental diagnosis of AF may trigger symptoms in susceptible patients as they become aware of a heart condition, 137 and even failed AF ablation may have a placebo effect in such patients. 138 A challenge with rhythm control (e.g.…”
Section: Atrial and Ventricular Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether (and how) asymptomatic AF patients could benefit from AF ablation still needs to be established. Incidental diagnosis of AF may trigger symptoms in susceptible patients as they become aware of a heart condition, 137 and even failed AF ablation may have a placebo effect in such patients. 138 A challenge with rhythm control (e.g.…”
Section: Atrial and Ventricular Remodelingmentioning
confidence: 99%
“…using electrical cardioversion) could identify apparently asymptomatic patients who had subconsciously adapted to AF by restricting their lifestyle or have atypical symptoms. 77,137 In many cases, a trial with an antiarrhythmic drug might be considered after cardioversion before considering ablation. Whereas these patients would likely experience symptomatic improvement after successful AF ablation, 138 a failed procedure may turn truly asymptomatic patients into symptomatic due to post-procedural atrial tachyarrhythmias (such a scenario has been reported in 24-34% of patients).…”
Section: Atrial and Ventricular Remodelingmentioning
confidence: 99%
“…These studies have, however, been widely debated, being generally underpowered to reveal a possible impact on the aforementioned outcomes in patients undergoing AFCA 5 or affected by crossovers between the study arms 6 . On the contrary, evidence from observational matched databases/registry studies suggest a net benefit of AFCA in terms of hard clinical endpoint reductions 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…15 A reduction in the mortality or stroke risk with AF ablation has not yet been shown. 16 Therefore, the only indication for AF ablation in the recent guidelines has been the presence of symptoms 5,15 In our series, the freedom from AF after the ablation was not inferior in the patient with silent paroxysmal AF as compared to that in those with symptomatic paroxysmal AF. However, two important questions remain because they were asymptomatic: (a) Were some incidences of recurrent AF missed?…”
Section: Ablation Of Silent Paroxysmal Afmentioning
confidence: 99%